Artefacts in cultural transmission: Evolutionary perspective - Aleksandra Nikolić (Etnoantropološki Problemi, 2018)
In this study, the existing body of knowledge related to the mechanisms of cultural evolution is analyzed in view of the role of artefacts in cultural transmission. It is focused primarily on the vertical transmission without inter-personal contact. Particular attention is given to the comparison between unit of culture and artefacts as its material expression, as well as to the studies of analogy between replication in genetic transmission and cultural transmission. It is found that retrieving cultural information from an artefact in absence of original transmitter still shows the principal characteristics of cultural transmission. This type of cultural transmission is of lower fidelity than synchronic transmission with inter-personal contact, since it relies on an artefact as a transmission medium, but can provide for cultural persistence and lay ground for adaptive modifications over time.